A revision of the conductive hearing loss in Cranium 4 from the Middle Pleistocene site of Sima de los Huesos (Burgos, Spain). Issue 135 (October 2019) - Conde-Valverde, Mercedes; Rosa, Manuel; Martínez, Ignacio; Marchamalo, Julio; Pantoja-Pérez, Ana; Quam, Rolf; Lorenzo, Carlos; Gracia-Téllez, Ana; García-Fernández, Alfredo; Arsuaga, Juan Luis; Rivera-Rodríguez, Teresa
Abstract: Pathological conditions have been previously documented in the Middle Pleistocene Sima de los Huesos hominins from northern Spain, and several of these have clear behavioral implications. Within this fossil assemblage, Cranium 4 shows bilateral external auditory exostoses which have been preliminarily interpreted as causing a significant hearing loss in this individual. If confirmed, this would be the oldest recorded case of deafness in human history and could have important implications for the antiquity of this condition, as well as social interactions. To further investigate this case, the current study presents 3D reconstructions of the entire outer and middle ear, based on computed tomography scans of both temporal bones in Cranium 4. We established the degree of stenosis in both external auditory canals, showing that in both cases the degree of stenosis is less than 52% of the original cross-sectional area of each canal. Based on clinical studies in living humans, the buildup of wax due to the degree of stenosis in Cranium 4 is unlikely to have caused frequent external ear infections. In addition, we estimated the pattern of sound power transmission up to 5 kHz in both ears relying on a comprehensive model developed in the bioengineering literature and which has been applied previously to the Sima de los Huesos hominins. The model was modified to account for the peculiar shape of the pathological external ear canals in Cranium 4. The results show that this pathology had little to no influence on the sound power transmission in this individual. Thus, we conclude that the exostoses present in both ears of Cranium 4 did not significantly affect their hearing.